Acute effects of angiotensin-converting enzyme inhibition versus angiotensin II receptor blockade on cardiac sympathetic activity in patients with heart failure - Azevedo, Eduardo R.; Mak, Susanna; Floras, John S.; Parker, John D. (American journal of physiology. Regulatory, integrative and comparative physiology, 2017)
The beneficial effects of angiotensin-converting enzyme (ACE) inhibitors and angiotensin II (ANG II) receptor antagonists in patients with heart failure secondary to reduced ejection fraction (HFrEF) are felt to result from prevention of the adverse effects of ANG II on systemic afterload and renal homeostasis. However, ANG II can activate the sympathetic nervous system, and part of the beneficial effects of ACE inhibitors and ANG II antagonists may result from their ability to inhibit such activation. We examined the acute effects of the ACE inhibitor captopril (25 mg, n = 9) and the ANG II receptor antagonist losartan (50 mg, n = 10) on hemodynamics as well as total body and cardiac norepinephrine spillover in patients with chronic HFrEF. Hemodynamic and neurochemical measurements were made at baseline and at 1, 2, and 4 h after oral dosing. Administration of both drugs caused significant reductions in systemic arterial, cardiac filling, and pulmonary artery pressures ( P < 0.05 vs. baseline). There was no significant difference in the magnitude of those hemodynamic effects. Plasma concentrations of ANG II were significantly decreased by captopril and increased by losartan ( P < 0.05 vs. baseline for both). Total body sympathetic activity increased in response to both captopril and losartan ( P < 0.05 vs. baseline for both); however, there was no change in cardiac sympathetic activity in response to either drug. The results of the present study do not support the hypothesis that the acute inhibition of the renin-angiotensin system has sympathoinhibitory effects in patients with chronic HFrEF.